The Peruvian Judicial Power as an object of study for the quality of democracy and the administration of justice in Peru. Advantages and difficulties - Salas Villalobos, Sergio (2012)
This brief provides thoughts on the model of the Peruvian Judicial system, as a member of a democratic system of a wider spectrum that requires solid bases for its institutionalization. We address the weaknesses of the system which continues to exist despite the personal efforts of some judges directing this process over the last few years. Although we have developed the method to identify judicial systems in other protocols, we believe that since it aims to provide a political view of the judicial system in Peru, the purpose of this paper now requires their definition in a political context